Respon Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) Terhadap Pemberian Kompos Azolla (Azolla pinnata R. Br.) - Andreas Parlindungan Tua Simarmata; Lisa Mawarni; Haryati Haryati (Universitas Sumatera Utara, 2018)
ABSTRACT Shallots production in Indonesia is still low due to the use of less seeds and poor planting medium. Utilization of superior seed variety and azolla as organic fertilizer with N can be used as a solution. This research aims to obtain the dose of azolla compost which can increase the growth and shallots production. The research was in Medan with ± 25 meters above sea level, from Maret until June 2016. This research used non factorial randomized block design namely no azolla compost, azolla 12,5 g / polybag, 25 g / polybag, 37,5 g / polybag, 50 g / polybag, and 62,5 g / polybag. Parameter observed were plant length, number of leaves per clump, number of tillers per clump, diameter of the bulbs, wet bulb weight and dry bulb weight. The result showed that applicatian of azolla compost only had a significant effect on parameter plant height 6 week after plant. While parameter plant height 2 – 5 week after plant, number of leaves 2 – 6 week after plant, number of tillers per clump 2 – 6 week after plant, diameter of the bulbs, wet bulb weight and dry bulb weight were not significant effect. Keywords: azolla compost, shallot